Enhancement of Rotated Face Detection and Image Duplication Methods - Tioh, Keat Soon; Hasan Basari, Abd Samad; Hussin, Burairah (2014)
Pattern detection plays an important role in digital image. Scale invariant feature transform (SIFT) for image duplication method and face detection has been successfully applied in real world problem. However, the face detection method is limited to rotation invariant and SIFT method is limited to the speed performance. In order to overcome the issue above, this paper proposed enhancement of SIFT for image duplication detection and rotation invariant face detection into pattern detection method. The comparison result of the experiment shows that proposed solutions are better performance.